Evaluation of organ donation process and affecting factors in COVID-19 pandemic - Kılınç, Gökhan; Çöken, Fuat (The European Research Journal, 2023)
Objectives: More than six million people worldwide are affected by end-stage organ failure and the COVID-19 pandemic has dramatically changed organ and tissue donation. Methods: The data of patients diagnosed with brain death between July 2018-March 2020 (pre-pandemic period) and April 2020-December 2021 (pandemic period) were analyzed retrospectively. Donor characteristics, laboratory levels, time from intensive care admission to determination of brain death, time to family approval, family approval rates and organ types were analyzed. Results: The mean age of 56 patients with pre-pandemic diagnosis of brain death was 61.82 ± 21.39 years, 37 (63%) patients were donors and 53 organs were obtained. Mean age of 39 patients diagnosed with brain death during the pandemic was 58.26 ± 18.02 years and 38 organs were obtained from 21 (52.5%) donors. Between the two periods, there was a decrease of 30.35% in the diagnosis of brain death, 43.24% in the number of donors and 26.41% in the number of organs supplied. The most common cause of brain death was intracranial hemorrhage during both periods. While the time elapsed between family interview and surgery was 9.33 ± 2.19 hours before the pandemic, it was 15.29 ± 4.28 hours during the pandemic period (p = 0.01). There was a significant difference between C-reactive protein levels at the time of diagnosis of brain death (p < 0.05). Staphylococcus haemolyticus was most frequently seen in blood culture. Conclusions: Brain death and organ donation have decreased significantly during the pandemic period compared to previous years, similar to research conducted in different countries and regions. Due to COVID-19, prolonged stays in the intensive care unit (ICU) may pose a risk of infection in ICU donors, and care should be taken in terms of donor loss.